Phytoremediation technologies promising for the restoration of agricultural lands damaged by military actions - N. Martynova; T. Kolombar (Regulatory Mechanisms in Biosystems, 2025)
Soil disturbance as a result of military action can range from a short-term reduction in fertility to complete destruction of the soil. A special problem is the restoration of agricultural soils. The most promising way to solve this issue is to use phytoextraction and phytostabilization methods, especially those that combine remediation measures with simultaneous economic benefits. R e cently, among phytoextraction strategies, preference has been given to growing plants that do not have the ability to hyperacc u mulate, but which , due to their rapid growth and the formation of a large biomass, can remove toxicants from the soil in large quantities. The idea of combining the restoration of contaminated lands with the production of biomass for phytomining and renewable energy is especially attractive. Phytostabilization strategies can be implemented using useful plants that do not acc u mulate pollutants in the final raw material, for example, some agricultural, forage and pasture crops ( Vicia villosa , Secale cereale , Zea majus , Lupinus luteus , Festuca sp . , Lolium perenne , etc.), energy crops ( Spartina pectinata , Miscanthus sp., etc.), essential oil plants ( Mentha×piperita , Melissa officinalis , Marrubium vulgare ). The attention of scientists is also drawn to the search for promising soil additives and the study of their application rates in order to improve soil conditions and increase biomass yields.